2021
DOI: 10.3390/polym13111830
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Loading History and Soil Type on the Normal Contact Behavior of Natural Sand Grain-Elastomer Composite Interfaces

Abstract: Recycled rubber in granulated form is a promising geosynthetic material to be used in geotechnical/geo-environmental engineering and infrastructure projects, and it is typically mixed with natural soils/aggregates. However, the complex interactions of grains between geological materials (considered as rigid bodies) and granulated rubber (considered as soft bodies) have not been investigated systematically. These interactions are expected to have a significant influence on the bulk strength, deformation charact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 86 publications
(139 reference statements)
5
10
0
Order By: Relevance
“…Representative scanning electron microscope images of the two sands are given in supplementary Figure 1. Tian et al [66] examined the surface roughness (in terms of RMS) values of LBS and Blue sand and reported that Blue sand has grains with much rougher surfaces. RMS roughness values for LBS have been reported within a range of 0.20 to 0.45 μm [66][67][68], however Blue sand grains have, approximately, five to ten times higher RMS roughness compared with LBS [66].…”
Section: Materials Used For the Macroscopic Experimentsmentioning
confidence: 99%
“…Representative scanning electron microscope images of the two sands are given in supplementary Figure 1. Tian et al [66] examined the surface roughness (in terms of RMS) values of LBS and Blue sand and reported that Blue sand has grains with much rougher surfaces. RMS roughness values for LBS have been reported within a range of 0.20 to 0.45 μm [66][67][68], however Blue sand grains have, approximately, five to ten times higher RMS roughness compared with LBS [66].…”
Section: Materials Used For the Macroscopic Experimentsmentioning
confidence: 99%
“…This material has origin a sedimentary rock and it consists, similar to Sydney sand, of quartz-based particles with an average size of 2 to 4 mm. Characterization of LBS particles has been presented in previous studies on sand grain contacts and sand-polymer-based contacts [56][57][58][59]. It is noted that the decision to use LBS particles for the grain-scale tests was that the micromechanical apparatus to test particle-to-particle contacts can accommodate sizes of grains, in general, between 1 and 5 mm, so it was preferable to use LBS than Sydney sand or White sand.…”
Section: Test Materialsmentioning
confidence: 99%
“…On the other hand, less microscopic energy dissipation (as hysteretic mechanism), may lead to the opposite result at the macroscopic level leading to increased bulk damping in the resonant column tests of fiber-sand mixtures. Especially for composite interfaces of sand particles sliding on polymeric surfaces, similar to that of sand-rubber composite systems, the response of sand-fiber-sand interfaces may have also been contributed by viscous mechanisms which cause an increased bulk energy dissipation [59,70]. In general, at small-strain perturbations, the results in the present study suggest a negative correlation between bulk damping and interparticle friction (which in turn, is related with the extended slip displacements in fiber-sand composite interfaces).…”
Section: Multi-scale Insightsmentioning
confidence: 99%
“…Given that LBS and CDV are two sands of extremely different morphological characteristics and properties (though both materials are "rough" in a contact mechanics context), the very similar friction values between LBS-rubber and CDV-rubber imply that the magnitude of surface roughness and other characteristics, which may contribute to the differences between the two sands, are very minor contributing mechanisms in the frictional behavior of the composite interfaces, and that rubber, which is a very soft material with viscous behavior controls the friction. It is noted that Tian et al [81] quantified the surface roughness of rubber particles and reported an average (RMS) value of approximately 2 microns, which is about 2 times greater than that of the CDV particles and 8 times greater than that of LBS. Despite some influence of the sand grain type, the study by [81] also reported a dominance of the rubber in the normal contact response of sand grain-rubber interfaces subjected to cyclic loading, with an approximate reduction of the normal contact stiffness of one to two orders of magnitude from the pure sand grain contacts to sand grain-rubber composite interfaces (note that the study by [81] investigated a broad range of sand particles, from LBS, to weathered granitic particles as well as grains from basaltic crushed rock).…”
Section: Monotonic Shearing Of Composite Interfaces: General Observations On Frictionmentioning
confidence: 99%
“…It is noted that Tian et al [81] quantified the surface roughness of rubber particles and reported an average (RMS) value of approximately 2 microns, which is about 2 times greater than that of the CDV particles and 8 times greater than that of LBS. Despite some influence of the sand grain type, the study by [81] also reported a dominance of the rubber in the normal contact response of sand grain-rubber interfaces subjected to cyclic loading, with an approximate reduction of the normal contact stiffness of one to two orders of magnitude from the pure sand grain contacts to sand grain-rubber composite interfaces (note that the study by [81] investigated a broad range of sand particles, from LBS, to weathered granitic particles as well as grains from basaltic crushed rock).…”
Section: Monotonic Shearing Of Composite Interfaces: General Observations On Frictionmentioning
confidence: 99%